2023
DOI: 10.3390/jcm12134442
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Colitis: Pathogenesis and Diagnosis

Abstract: Microscopic colitis is a type of inflammatory bowel disease and is classified as either collagenous colitis or lymphocytic colitis. The typical presentation is chronic watery diarrhea. The disease occurs more frequently in women aged 60–65 years and is increasing in incidence. The pathophysiology of microscopic colitis remains poorly understood and has not been well-described with possible several pathogeneses. To date, the diagnosis of microscopic colitis depends on histological tissue obtained during colonos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…They revealed that PPI users have a significantly higher risk of IBD (adjusted OR = 2.43, 95%CI: 1.18-5.02). A subgroup analysis showed that collagenous colitis (CC) and lymphocytic colitis (LC) can be considered attenuated forms of IBD[ 76 ]. The significant correlations between PPI exposure and the risk of CC and LC were 4.73 (95%CI: 1.99-11.22) and 3.77 (95%CI: 2.91-4.87), respectively.…”
Section: Clinical Epidemiology Of the Effects Of Ppis On Ibdmentioning
confidence: 99%
“…They revealed that PPI users have a significantly higher risk of IBD (adjusted OR = 2.43, 95%CI: 1.18-5.02). A subgroup analysis showed that collagenous colitis (CC) and lymphocytic colitis (LC) can be considered attenuated forms of IBD[ 76 ]. The significant correlations between PPI exposure and the risk of CC and LC were 4.73 (95%CI: 1.99-11.22) and 3.77 (95%CI: 2.91-4.87), respectively.…”
Section: Clinical Epidemiology Of the Effects Of Ppis On Ibdmentioning
confidence: 99%